Transformational Leadership Directly and Indirectly Effect on Nurse Performance: Organizational Cultural as Intervening Variables - Nur Hidayah; Eva Nur Fadila (Asian Social Work Journal, 2019)
A nurse performance greatly determines the quality of health services in a hospital. The purpose of this study was to prove the influence of transformational leadership on nurse performances, both directly and indirectly through organizational culture and work motivation. The research method used was a quantitative approach with cross-sectional design. The number of samples consisted of 86 nurses in a private hospital. Data collection used a questionnaire. Data analysis techniques used Partial Least Square Structural Equation Modeling (PLS-SEM). Research results shew that transformational leadership had a positive and significant effect on nurse performance both directly and indirectly through organizational culture and work motivation). The study results have shown that Transformational Leadership is effect on Organizational Culture. Transformational Leadership is effect on Work Motivation. Transformational Leadership, Organizational Culture, and Work Motivation are effect on Nurses Performance. Organizational culture mediated the effect of the transformational leadership on performance.